Internet Scale DoS Attacks - Berat KURAR; Radwan TAHBOUB (International Journal of Applied Methods in Electronics and Computers, 2015)
Internet scale DoS attack is a new evolution of conventional flooding DoS attack with the inspiration of shutting down the Internet due to its vulnerable infrastructure. Past DoS attacks directly attacked the victim, usually a single host. Consequently, defences were designed to identify the excessive traffic or filter illegitimate traffic. From the early two thousand, Internet scale DoS attacks started to appear. They aimed to disable highly connected routers or large links with a legitimate action in the form of low-rate traffic or high-rate wanted traffic with protocol messages that are unfiltered by congestion control. The latter can be more devastating due to its global impact therefore attracts the attention of researchers and some applications are now available. The goal of this paper is to introduce Internet scale DoS attack and to survey its theoretical underpinnings and experimental applications. Several attacking techniques will be presented, as well as their effects on the connectivity of the Internet. A comparison will be carried out among them to expose their pros and cons in order to study the possibility of their integration via usage of several botnets for destroying the Internet connectivity. Our discussion aims to clarify new directions that DoS, DoS defence and Internet design research can follow.